217 - SOLID WASTE GENERATED IN THE UNIVERSITIES' ENVIRONMENT: A PROBLEM TO BE FACED (Fiep Bulletin - online, 2011)
Solid waste is one of the major environmental problems experienced by humans, mainly because it does not end when the "garbage" is to collect and persisted until the final destination receives. The solid waste generated in the university encompasses the urban solid waste, industrial and health care. Are generated in the administrative sectors of education (classrooms and laboratories), to support academic activities, resulting in a multitude of waste to be collected and disposed properly. It is common in these environments the disposal of carcasses of computers, appliances and laboratory, as well as batteries and fluorescent lamps. It can also be generated waste classified as Class I (hazardous) from laboratories in chemistry, biology and physics. Minimizing the generation of waste at source is considered one of the main actions that should be part of the proposed solutions. Should be based on the principle of preservation, seeking ways to avoid the generation of large quantities of waste. The effects of environmental pollution are far more complex and diffuse than one might assess at first, its aftermath and widespread, may also be chronic and cumulative, becoming more complex action to clean up. Without the conscious participation of every individual, are not going to change the form of behavior, or promote the reduction of the amount of waste generated. Clarification of individuals is necessary, to become allies in the transformation. For the definition of strategies, it is necessary to build a comprehensive knowledge of local reality of each group and the factors involved in the urban context.
Keywords: solid waste; universities; environmental